Countering Gender Stereotypes: The Power of the Main Female Character in Thor: Ragnarok Movie (2017) - Fitriyah, Lailatul; Sukarno, Sukarno; Setiarini, Riskia; Tallapessy, Albert (Journal of Language and Literature, 2024)
Gender stereotypes constructed by society are detrimental for women. Women were seen as weak and underestimated by society (the PEW Research Center’s survey in 2017). This study aims to discover how a film entitled Thor: Ragnarok (2017) countered gender stereotypes through the portrayal of the main female character, Hela, and to reveal the reason behind such portrayal of Hela. This study is a qualitative study because the data are qualitative data. The data of this study are clauses collected from the movie subtitles, containing Hela’s power to counter gender stereotypes. This study applied Fairclough’s Critical Discourse Analysis (three-dimensional framework), supported by Halliday’s Systemic Functional Linguistics (SFL), which focused on the transitivity system for the first-dimension analysis. After doing the three-dimensional analysis, it is found that Hela’s character in the movie is portrayed as opposing gender stereotypes. Hela is represented as strong, brave, and feared. These traits are against the stereotype of women described as weak, fearful, and underestimated. The reason behind the portrayal of Hela as a strong woman is to promote the feminism spirit to the people in that women should be empowered, in line with the goal of the United Nations (UN) Women and the UN Foundation that protect women's rights and supports women in achieving gender equality.